2007
DOI: 10.1007/s11581-007-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of polycrystalline TiO2. Prolonged oxidation kinetics

Abstract: The equilibration kinetics for polycrystalline TiO 2 was monitored during prolonged oxidation at 1,323 K and p(O 2 ) = 75 kPa using the measurements of the electrical conductivity and thermoelectric power. The determined kinetic data indicate the presence of two kinetics regimes; the Regime I (rapid kinetics) and the Regime II (slow kinetics). The prolonged oxidation of TiO 2 is considered in terms of the formation of Ti vacancies at the surface and their subsequent transport into the bulk. This effect, also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 7 publications
(20 reference statements)
3
36
0
Order By: Relevance
“…Thus, oxygen vacancies and titanium interstitials mostly dominate the defect chemistry of Titania due to their lower formation enthalpies and it leads to n-type conductivity in Titania. Formally, titanium vacancies are thermodynamically reversible defects (theoretically); hence, they are usually obtained by quenching to make it as an irreversible defect [58][59][60][61][62][63]. Based on the above discussion, it is understood that an appropriate growth condition is required to incorporate the required defects in Titania.…”
Section: Electron Holesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, oxygen vacancies and titanium interstitials mostly dominate the defect chemistry of Titania due to their lower formation enthalpies and it leads to n-type conductivity in Titania. Formally, titanium vacancies are thermodynamically reversible defects (theoretically); hence, they are usually obtained by quenching to make it as an irreversible defect [58][59][60][61][62][63]. Based on the above discussion, it is understood that an appropriate growth condition is required to incorporate the required defects in Titania.…”
Section: Electron Holesmentioning
confidence: 99%
“…The defects in Titania are induced either by an in-situ control (defects creation during synthesis or ex-situ controlled (the incorporation of defects after preparation) mechanism. The reported methods to produce Ti interstitial in Titania are prolonged oxidation (1000 • C for 24 h) [60,[64][65][66][67]. The state-of-the-art method to prepare reduce Titania (oxygen deficient) include energetic ion or electron beam implantation, UV irradiation, heating TiO 2 under vacuum, thermal annealing to high temperatures (above 500 K), reducing conditions (C, H 2 ), plasma-treating, laser, and high-energy particle (neutron, Ar + , electron, or γ-ray) bombardment, chemical vapor deposition, vacuum activation, metal reduction, electrochemical reduction, partial oxidation starting from Ti, Ti(II) and Ti(III) precursors, etc.…”
Section: Experimental Approaches To Generate Defects In Titaniamentioning
confidence: 99%
“…24,29 The electrical conductivity changes as a function of time during isothermal oxidation of TiO 2 at 75 kPa at 1323 K, shown in Fig. This is the case when the concentrations of all lattice species, including point defects, correspond to equilibrium.…”
Section: Transport Kinetics Of Defects In Tiomentioning
confidence: 99%
“…The studies of Bak et al 13 and Nowotny et al 24,28,29 have shown that the intrinsic defect disorder of TiO 2 includes titanium vacancies as well. It has been documented that properties of pure TiO 2 may only be explained assuming the presence of three types of ionic defects (oxygen vacancies, titanium interstitials and titanium vacancies) and both types of electronic charge carriers.…”
Section: Defect Equilibriamentioning
confidence: 99%
“…[8][9][10][11][12] The recent studies show, however, that prolonged oxidation of rutile leads to the formation and propagation of titanium vacancies, which are acceptor type defects. 13,14 Their ionisation results in the formation of electron holes, which are associated with p-type conduction of rutile. Therefore, the real chemical formula of titanium dioxide, reflecting the non-stoichiometry in both oxygen and titanium sublattices, is better represented as Ti 1¡y O 22x .…”
Section: Introductionmentioning
confidence: 99%